Role of Bleach Sedimentation Technique for the Diagnosis of Tuberculosis. (KYAMC Journal, 2017)
Tuberculosis remains a major threat to world health. The main aim of this study was to improve the microscopic detection of AFB from sputum by Bleach sedimentation technique using household bleach. This was a cross sectional type of study conducted for a period of one year from July 2010 to June 2011 in the Department of Laboratory Services, Khwaja Yunus Ali Medical College Hospital (KYAMCH), Sirajgonj. A total of 115 clinically suspected tuberculosis patients aged between 7-85 years were included in the study. Among them 35 (30.4%) patients had TB positive by routine (Direct microscopy) method; whereas, by bleach concentration method 42 (36.5%) were found positive; diagnosing 07 additional patients. The rise of 16.7% in sputum positivity by bleach sedimentation microscopy over the direct smear microscopy was found to be statistically significant (p=